MORPHOLOGY OF FOLKLORE BATU NAGA LAMPUNG - Sri Nursari; Slamet Subiyantoro; Kundharu Saddhono (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study was to analyze the morphology of folklore based on Vladimir Propp's theory and method of researching Narratology structure including the structure of the actor's action function, the function in the action environment, and the scheme. This research method is descriptive qualitative and the method developed by Vladimir Propp. The object of research is the Batu Naga Lampung folklore. The technique of data collection is done by the documentation technique through a literature study. Data analysis techniques use the flow method that is data reduction, data presentation, and concluding. The results of the study found there are 26 functions of the perpetrators' actions that are distributed into 6 action environments.